A biodegradable thermoset polymer made by esterification of citric acid and glycerol. Issue 5 (24th June 2013) - Halpern, Jeffrey M.; Urbanski, Richard; Weinstock, Allison K.; Iwig, David F.; Mathers, Robert T.; von, Horst A.
Abstract A new biomaterial, a degradable thermoset polymer, was made from simple, economical, biocompatable monomers without the need for a catalyst. Glycerol and citric acid, nontoxic and renewable reagents, were crosslinked by a melt polymerization reaction at temperatures from 90 to 150°C. Consistent with a condensation reaction, water was determined to be the primary byproduct. The amount of crosslinking was controlled by the reaction conditions, including temperature, reaction time, and ratio between glycerol and citric acid. Also, the amount of crosslinking was inversely proportional to the rate of degradation. As a proof‐of‐principle for drug delivery applications, gentamicin, an antibiotic, was incorporated into the polymer with preliminary evaluations of antimicrobial activity. The polymers incorporating gentamicin had significantly better bacteria clearing of Staphylococcus aureus compared to non‐gentamicin gels for up to 9 days. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 1467–1477, 2014.